Rationales for public private partnership (PPP) implementation in Malaysia - Ismail, Suhaiza; Haris, Fatimah Azzahra (Emerald, 2014)
Purpose – There are two objectives for the present study. First, it examines the rationale for implementation of public private partnerships (PPP) in Malaysia. Second, it investigates the differences among perceptions of the public and private sectors, in relation to the rationales for implementing PPP in Malaysia.